2019
DOI: 10.18549/pharmpract.2019.4.1616
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an instrument designed to measure factors influencing physician prescribing decisions

Abstract: Background:Previous attempts to develop an instrument to measure factors that influence prescribing decisions among physicians were relatively insufficient and lacked validation scale.Objective:We present a new tool that attempts to address this shortcoming. Hence, this study aims to develop and validate a self-administrated instrument to explain factors that influence the prescribing decisions of physicians.Methods:The questionnaire was developed based on literature and then subjected to an exhaustive assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 59 publications
1
13
0
1
Order By: Relevance
“…Furthermore, DTCPA has an increasing influence on physician-patient relationships and PHP. PHP has been influenced by medico marketing and other variables such as pair influence, pharmacy factor, and patient demand as it has evolved by physicians over many years of experience (Murshid et al, 2019).Consequently, the study has concluded that:…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, DTCPA has an increasing influence on physician-patient relationships and PHP. PHP has been influenced by medico marketing and other variables such as pair influence, pharmacy factor, and patient demand as it has evolved by physicians over many years of experience (Murshid et al, 2019).Consequently, the study has concluded that:…”
Section: Discussionmentioning
confidence: 99%
“…The current study's research design was based on Creswell (2014) mixed method of sequential explanatory approach. The study's first phase was quantitative with primary data collected through a questionnaire adapted from Murray et al (2004), Murshid, Mohaidin and Zayed (2019). The instrument underwent some contextual changes and a thorough validation process was carried out using psychometric statistics, such as reliability and validity on a pilot data set.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the marketing efforts of pharmaceutical companies, most of the physicians emphasize availability of information about a drug, followed by the brand of the drug and effectiveness of the medical promotion officers of pharmaceutical companies. [28] In prescribing medications, the physicians also take into consideration factors such as patients' requests and expectations. Meanwhile, pharmacist-related factors, such as the relationship with pharmacists and their trustworthiness, also play an influential role in physicians' prescription of medications.…”
Section: Discussionmentioning
confidence: 99%
“…But prescribing behavior is not merely associated with the clinical condition; rather it is a complex process involving several factors that influence prescribing decisions. [26,27] For example, Murshid et al [28] identified 13 factors that influence physicians' prescribing behavior. They divided the factors into four categories: marketing efforts (information on a drug, brand of a drug, sales promotion, the effectiveness of medical representatives); patient characteristics (patients' request, patients' expectation); pharmacist-related factors (pharmacistphysician collaboration, pharmacists exerting power, trustworthiness); and contextual factors (drug characteristics, cost-benefit of drug, physician habit persistence).…”
Section: Introductionmentioning
confidence: 99%